Peroxisome Proliferator Activated Receptor Ligands as Regulators of Airway Inflammation and Remodelling in Chronic Lung Disease - Jane Elizabeth Ward; Xiahui Tan (PPAR Research)
Inflammation is a major component in the pathology of chronic lung diseases, including asthma. Anti-inflammatory treatment with corticosteroids is not effective in all patients. Thus, new therapeutic options are required to control diverse cellular functions that are currently not optimally targeted by these drugs in order to inhibit inflammation and its sequelae in lung disease. Peroxisome proliferator activated receptors (PPARs), originally characterised as regulators of lipid and glucose metabolism, offer marked potential in this respect. PPARs are expressed in both lung infiltrating and resident immune and inflammatory cells, as well as in resident and structural cells in the lungs, and play critical roles in the regulation of airway inflammation. In vitro, endogenous and synthetic ligands for PPARs regulate expression and release of proinflammatory cytokines and chemoattractants, and cell proliferation and survival. In murine models of allergen-induced inflammation, PPARα and PPARγ ligands reduce the influx of inflammatory cells, cytokine and mucus production, collagen deposition, and airways hyperresponsiveness. The activity profiles of PPAR ligands differ to corticosteroids, supporting the hypothesis that PPARs comprise additional therapeutic targets to mimimise the contribution of inflammation to airway remodelling and dysfunction.